Evaluation of the relationship between serum apelin levels and vitamin D and mean platelet volume in diabetic patients - Kiskac, MUHARREM; Buyukaydin, BANU; KISKAÇ, MUHARREM; Zorlu, MEHMET; ZORLU, MEHMET; Cakirca, MUSTAFA; ÇAKIRCA, MUSTAFA; KARATOPRAK, CUMALİ; KARATOPRAK, CUMALİ; KESGIN, Sidika; BÜYÜKAYDIN, BANU; YAVUZ, Erdinc; et al. (My University, 2014)
Objectives. - It was reported that Vitamin D deficiency was associated with a greater risk of cardiometabolic diseases, obesity, impaired glucose tolerance and diabetes mellitus type 2, arterial hypertension, and dyslipidemia. Apelin is an adipocytokine suspected to have a role in skeletal muscle glucose utilization and glycemic regulation which may be a promising treatment modality for diabetes. It was recently reported that increased mean platelet volume (MPV) was emerging as an independent risk factor for thromboembolism, stroke, and myocardial infarction. In patients with diabetes, MPV was higher compared with the normal glycemic controls; in addition, it has been proposed that an increase in MPV may play a role in the micro- and macro-vascular complications related to diabetes. We postulated that deficiency in Vitamin D levels might be associated with higher MPV and lower serum apelin levels leading a further increase in insulin resistance in diabetic patients. So, we aimed to investigate Vitamin D levels, MPV and serum apelin levels in diabetic patients and their correlations between each other. Materials and method. - This is a cross-sectional study design. Seventy-eight patients with Diabetes Mellitus type 2, admitted to our outpatient clinic of internal medicine department at Bezmialem Vakif University, were included in our study. Forty-one patients were female; 37 patients were male. Serum apelin levels, fasting glucose levels, urea, creatinine, triglycerides, total cholesterol, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), fasting serum insulin level, HbAl(c), free T3, free T4, TSH, vitamin D (25-OH Vitamin D) and complete blood counts were analyzed in all subjects. Results. - Each sex was analyzed separately. We found that a positive correlation existed between serum apelin levels and BMI in female patients. (r: 0.380, P: 0.014) There was also a significant positive correlation between MPV and HbAl, and fasting glucose levels and a negative correlation between MPV and PLT. (r: 0.377, P: 0.021; r: 0.395, P: 0.014; r: 0.401, P: 0.011; respectively) We failed to show a significant relationship between serum vitamin D levels, serum apelin levels and MPV in patients with diabetes mellitus type 2. Conclusion. - We failed to show an association between vitamin D, apelin and MPV higher volumes of which may have a role in cardiovascular complications related to diabetes by increasing platelet activation. (C) 2014 Published by Elsevier Masson SAS.